2019
DOI: 10.1186/s12885-019-6315-8
|View full text |Cite
|
Sign up to set email alerts
|

Dual time point 18F-fluorodeoxyglucose positron emission tomography/computed tomography fusion imaging (18F-FDG PET/CT) in primary breast cancer

Abstract: Background: To evaluate the clinicopathological and prognostic significance of the percentage change between maximum standardized uptake value (SUV max) at 60 min (SUV max 1) and SUV max at 120 min (SUV max 2) (ΔSUV max %) using dual time point 18 F-fluorodeoxyglucose emission tomography/computed tomography (18 F-FDG PET/CT) in breast cancer. Methods: Four hundred and sixty-four patients with primary breast cancer underwent 18 F-FDG PET/CT for preoperative staging. ΔSUV max % was defined as (SUV max 2 − SUV ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…RI has also been reported to be correlated with prognosis in patients with lung cancer, cholangiocarcinoma, and lymphoma [ [23] , [24] , [25] ]. However, only one study has reported a relationship between RI and prognosis in patients with breast cancer [ 11 ]. The study suggested that the combination of SUVmax1 and RI was more useful for predicting prognosis than SUVmax1 alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RI has also been reported to be correlated with prognosis in patients with lung cancer, cholangiocarcinoma, and lymphoma [ [23] , [24] , [25] ]. However, only one study has reported a relationship between RI and prognosis in patients with breast cancer [ 11 ]. The study suggested that the combination of SUVmax1 and RI was more useful for predicting prognosis than SUVmax1 alone.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that dual-phase FDG PET/CT would more accurately estimate the prognosis of patients with operable breast cancer than single-phase examination. One retrospective study has reported that the early-phase SUVmax and rate of SUVmax change identify patients with a worse prognosis [ 11 ]. However, the report had the limitation of an insufficient follow-up period.…”
Section: Introductionmentioning
confidence: 99%
“…It should be remembered that [ 18 F]F-FDG is not a specific radiotracer for BC or malignancy in general, and numerous conditions may lead to false-positive results, such as infection, fibroadenoma, ductal adenoma, inflammatory granulomatous mastitis, and fibrocystic changes ( 23 28 ). Some authors investigated the use of late imaging to improve specificity, since uptake usually increases on delayed images in case of malignancy, while it often decreases in inflammatory lesions ( 29 , 30 ). However, [ 18 F]F-FDG can only provide information on cellular metabolism and not on other tumor characteristics, such as proliferation and receptor status.…”
Section: Molecular Imaging Of Glycolysismentioning
confidence: 99%
“…A high level of 18 F-FDG accumulation on PET/CT is considered to represent the active form of tumor cells. Therefore, the maximum standardized uptake value (SUVmax) of primary cancer on FDG PET/CT may be used to estimate the outcomes of patients [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of FDG PET/CT for the detection of malignant lesions is high; however, FDG also accumulates in inflammatory lesions [ 9 , 10 , 11 ]. To overcome this limitation, previous studies demonstrated the efficacy of measuring 18 F-FDG uptake levels at dual time points (DTP) [ 7 , 12 , 13 ]. The 18 F-FDG uptake level at a later phase (2–3 h after the injection) is more likely to increase specifically in malignant tumors and decrease in benign tumors [ 14 ].…”
Section: Introductionmentioning
confidence: 99%